The Integration of Faith and National Identity: A Comprehensive Study on Islamic Patriotism and Its Theological Implications - Mahmudulhassan, Mahmudulhassan; Rahmawati, Siti; A'yun Tamami, Fauziyah Qurrota (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
A fundamental love and devotion for one’s nation, patriotism takes many forms in different cultures and religions. In the framework of Islam, which has more than 1.8 billion adherents worldwide, faith and patriotism interact, offering special opportunities and difficulties. This research investigates Muslim conceptions and manifestations of patriotism, drawing on historical viewpoints, theological underpinnings, and contemporary interpretations of allegiance and national identity. Islamic teachings, which are based on the Quran, Hadiths, and academic interpretations, strongly emphasize defending and preserving one's native territory while promoting social welfare, justice, and harmony. And the well-being of the community. This study emphasizes how social norms, historical narratives, and education all play a part in moulding the sense of patriotism in Islamic environments. The study seeks to offer a thorough knowledge of Islamic patriotism by analyzing the complex relationship between commitment to Islamic values and patriotism. The results imply that when social justice, compassion, and peaceful cohabitation are prioritized, Islam not only accepts but actively promotes patriotism. This well-rounded strategy fosters the peaceful fusion of national and religious identities by enabling Muslims to contribute significantly to their communities while maintaining their religious convictions.